Russula swatica: A new species of Russula based on molecular, light microscopy, and scanning electron microscopy analyses from Swat Valley of Khyber Pakhtunkhwa province of Pakistan. Issue 10 (3rd July 2019) - Sarwar, Samina; Aziz, Tanzeela; Hanif, Muhammad; Ilyas, Sobia; Shaheen, Shabnum
Abstract: Himalayan range of Pakistan is one of the diversity rich hotspots of the world. Many areas are yet to be explored here to discover new species of organisms including fungi. During present research, Swat District of Pakistan was explored for fungal diversity. One new species of mushroom Russula swatica (Russulales) is described from Himalayan range of Pakistan and analyzed by light microscopy and scanning electron microscopy as well as by molecular markers. A comprehensive description, photographs, and comparisons with morphologically similar and phylogenetically related species are provided. Conclusions of its phylogenetic relationships within the genus are provided based on the sequence of the nuclear internal transcribed spacer region. Abstract : New mushroom discoveries from unattended and neglected areas of Pakistan. How new discoveries are shaking up fungal classification? Genetic profiling of Russulales of Pakistan. Scientific recognition to Pakistan in the world. New mushroom species may lead to new products for medicine and industry.